Performance evaluation of different cultivars of mandarin (Citrus reticulata) under arid irrigated region of Punjab - CHANDER, SUBHASH; KUMAR, KRISHAN; KAUR, MANVEEN; RATTANPAL, H S; ARORA, P K (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2022 and 2023 at Dr. J C Bakhshi Regional Research Station (Punjab Agricultural University, Ludhiana), Abohar, Punjab to evaluate the comparative performance of PDKV mandarin-5 (a clone of Nagpur mandarin), Nagpur mandarin, Kinnow and the recently recommended low seeded Kinnow mutant, PAU Kinnow 1. Kinnow displayed larger canopy volumes (21.9 and 25.5 m3) and higher fruit yield (32.5 and 65.6 kg/tree) during the two years. PAU Kinnow-1 showed on par yield to Kinnow. The lowest yield in both years was recorded in Nagpur mandarin. Among the fruit quality attributes, higher total soluble solids (TSS) were recorded in PAU Kinnow-1 (10.8 oB and 11.0 oB) during both years. Nagpur mandarin and PDKV-5 recorded TSS in the range of 7.1–7.8 oB. PAU Kinnow-1 and Kinnow also had higher juice content. Nagpur Mandarin in both years recorded highest ascorbic acid content (31.6 and 39.7 mg/100 ml juice). The lowest seed number (⁓ 3/fruit) was noted in PAU Kinnow-1. The results indicated that PAU Kinnow-1 due to its high yield potential (comparable to Kinnow) and superior fruit quality attributes (low seed content, high TSS and high juice content) holds promise for further area expansion under citrus fruits in Punjab.